KECERNAAN PROTEIN DAN ENERGI RANSUM BROILER YANG MENGGUNAKAN TEPUNG MAGGOT (HERMETIA ILLUCENS) SEBAGAI PENGGANTI TEPUNG IKAN - Rambet, Vanessa; Umboh, J. F.; Tulung, Y. L.R.; Kowel, Y. H.S. (Universitas Sam Ratulangi, 2016)
ENERGYANDPROTEIN DIGESTIBILITY OF BROILER CHICKEN CONSUMING MAGGOT (HERMETIA ILLUCENS) MEAL SUBSTITUTING FISH MEAL IN THE DIETS. As an animal feed, maggot from black soldier fly (Hermetia Illucens) has high protein and fat content. Yet, little is known about theÂ digestibility of energy and protein in the diet containing maggot. The present study wasÂ conducted to determine the effect of substitution of fish meal with maggot meal in the diets on energy and protein digestibility of broiler chicken. Twenty chicks were assingned to each dietary treatment which was replicated four times in a completely randomized design (CRD). Tretaments were formulated as follow: R0 = 100% fish meal (15% in the diet) + 0% maggot meal (0% in the diet); R1 = 75% fish meal (11,25% in the diet) + 25% maggot meal (3.75% in the diet); R2 = 50% fish meal (7.5% in the diet) + 50% maggot meal (7.5% in the diet); R3 = 25% fish meal (3.75% in the diet) + 75% maggot meal (11.25% in the diet); and R4 = 0% fish meal (0% in the diet) + 100% maggot meal (15% in the diet). Parameters measured were energy and protein digestibility. Energy and protein digestibility were calculated using the indicator (internal lignin) method. All data was submitted to the ANOVA procedure for completely randomized design. Differences were considered significantat (P< 0.05). The results showed that dry matter, energy, and protein digestibility were increased significantly (P < 0.05) compared to R0, R2, R3, and R4. No significant difference (P > 0.05)Â were found among R0, R2, R3, and R4. It can be concluded that the maggot flour is best used to the level of 25% replacing fish meal or 11.25% in the ration. However, the result of this study indicate that maggot flour can be used up to 100% replace fish meal in broiler chicken rations without any negative effect on digestibility of dry matter, energy, and protein. Keywords: Fish meal, maggot (Hermetia Illucens) meal, energy and protein digestibility.